Cost-Effective Performance Management for Washington State Pavement Assets. Issue 1 (2017) - Li, Jianhua; Luhr, David R.; Russell, Mark; Rydholm, Tim; Uhlmeyer, Jeff S.
The Washington State Department of Transportation (DOT) manages 18, 230 lane miles (29, 332 lane kilometers) of main-line roadway. In the past several years, the Washington State DOT has gone through an evaluation and modification of its pavement management practices. This paper presents the historical perspective on past Washington State DOT pavement practices and several strategies that were developed to improve the management of pavement assets. The Washington State DOT has been successfully preserving the long life of flexible pavements by applying thin hot-mix asphalt (HMA) mill and inlays on the basis of the concept that cracking in thicker HMA sections will primarily be top-down. Furthermore, using the framework developed by the evaluation of cost-effectiveness, several strategies have been implemented to improve the management of Washington State DOT pavement assets. These strategies are ( a ) converting 3, 000 lane miles (4, 827 km) from asphalt to chip seal resurfacing before the year 2025, ( b ) planning $850 million to $1.0 billion for rehabilitation and reconstruction for the aging concrete pavement network for the next 10 years with 50% of the concrete slated for reconstruction to be converted to flexible pavement using a crack and seat plus asphalt overlay process, and ( c ) applying strategic maintenance to reduce the annual cost by extending the service life of flexible pavements. These cost-effective strategies are expected to generate an overall annual cost savings of $80 million per year by 2025.